The Creation of an Artistic Documentary Picture Book to Communicate the Lifestyle and Cultural Identity of the Thai–Chinese Community in Yaowarat - สายกรรณ์ ดนัยฤทธิ์; อักษรณรงค์ ธราธร; ดีเจริญชิตพงศ์ จิรวิญญ์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research, titled “The Creation of an Artistic Documentary Photobook to Communicate the Lifestyle and Cultural Identity of the Thai-Chinese Community in Yaowarat,” aims to (1) study the history and way of life of the Yaowarat community, (2) create an artistic documentary photobook entitled “The Golden Light of Yaowarat,” and (3) present the identity of Yaowarat from a new perspective. Amid urban dynamics that have led to the gradual decline of cultural heritage, this study integrates empirical data with aesthetic interpretation through photographic sequencing, tonal control, and the use of accompanying text. The resulting work functions both as a medium for documenting social history and as an artistic expression that reflects cultural transformation with coherence. The findings reveal that • The content quality evaluation by subject-matter experts yielded an overall mean score of 3.80 with a standard deviation (S.D.) of 0.76, indicating a high level of quality; • The media quality evaluation by media experts showed an overall mean score of 4.00 with a standard deviation (S.D.) of 1.01, also indicating a high level of quality; and • 3. The satisfaction assessment among general audiences interested in the Yaowarat photobook resulted in a mean score of 74 with a standard deviation (S.D.) of 0.59, reflecting the highest level of satisfaction.